Validation of the Arabic Version of Asthma Numeracy Questionnaire (ANQ) Among Parents of Asthmatic Children: Factor and Rasch Analyses Study - Al-Qerem W; Jarab A; Al Bawab AQ; Eberhardt J; Alasmari F; Hammad A; Al-Zayadneh E; Al-Iede M; Al-sa’di L; Obidat R (Journal of Asthma and Allergy)
Walid Al-Qerem,1 Anan Jarab,2– 4 Abdel Qader Al Bawab,1 Judith Eberhardt,5 Fawaz Alasmari,6 Alaa Hammad,1 Enas Al-Zayadneh,7 Montaha Al-Iede,7 Lujain Al-sa’di,1 Raghd Obidat1 1Department of Pharmacy, Faculty of Pharmacy, Al-Zaytoonah University of Jordan, Amman, 11733, Jordan; 2College of Pharmacy, Al Ain University, Abu Dhabi, 112612, United Arab Emirates; 3AAU Health and Biomedical Research Center, Al Ain University, Abu Dhabi, 112612, United Arab Emirates; 4Department of Clinical Pharmacy, Faculty of Pharmacy, Jordan University of Science and Technology, Irbid, 22110, Jordan; 5Department of Psychology, School of Social Sciences, Humanities and Law, Teesside University, Middlesbrough, TS1 3BX, UK; 6Department of Pharmacology and Toxicology, College of Pharmacy, King Saud University, Riyadh, 12372, Saudi Arabia; 7Department of Pediatrics, School of Medicine, University of Jordan, Amman, JordanCorrespondence: Walid Al-Qerem, Department of Pharmacy, Faculty of Pharmacy, Al-Zaytoonah University of Jordan, Amman, 11733, Jordan, Email waleed.qirim@zuj.edu.joBackground: The increasing global prevalence of asthma necessitates effective disease management, with patients and their families playing a central role. Enhancing health literacy (HL) among caregivers is critical to improving asthma outcomes.Purpose: This study aimed to validate the Arabic version of the Asthma Numeracy Questionnaire (Ar-ANQ) to address the gap in HL assessment tools for Arabic-speaking populations.Patients and Methods: A total of 400 parents of children with asthma completed the Ar-ANQ at an outpatient respiratory clinic. Confirmatory factor analysis (CFA) and Rasch analysis were employed to evaluate the psychometric properties of the instrument.Results: CFA supported the unidimensional structure of the Ar-ANQ, with excellent model fit indices (χ²/df = 4.6, SRMR = 0.02, CFI = 0.99, GFI = 0.99, TLI = 0.96) and high internal consistency (Cronbach’s α = 0.82). Rasch analysis further demonstrated psychometric robustness, with high person and item separation reliabilities (0.74 and 0.99, respectively) and acceptable infit and outfit statistics.Conclusion: The Arabic version of the Asthma Numeracy Questionnaire (Ar-ANQ) is a reliable and valid instrument for assessing health literacy among parents of children with asthma.Keywords: Asthma Numeracy Questionnaire, asthma, health literacy, Arabic, pediatric